Hypermedia als Ansatz zur Realisierung von Lernparadigmen - Basińska, Ewelina (Die deutsche Sprache in vielfältigen Forschungsparadigmen. Beiträge polnischer Doktoranden anlässlich der 9. Linguistischen Tagung–Łódź, 09.05.2015, 2016)
The article considers the role of hypertext as a kind of hypermedia in CALL (Computer Aided Language Learning). The aim of hypertext is to motivate and promote learners critical thinking in order to solve problems or develop projects. The hypertext concept has to be adapted for foreign language acquisition and teachers have embraced it as a way to make good use of the Internet. This paper shows connections between hypertext-model and constructivist, behaviourist and cognitive approach in the significance of autonomy of participants of a didactic process.